Analisis Yuridis Komparasi Penyelesaian Kepailitan Transnasional di Singapura dan Malaysia dengan Penyelesaian di Indonesia - Sihotang, Angreina Larose; Mahmudah, Siti; Musyafa, Aisyah Ayu; Ardani, Mira Novana (Faculty of Law, Diponegoro University, 2023)
Transnational bankruptcy resolution is still a legal problem in ASEAN. This problem arises because there is no harmonization of legal regulations regarding transnational bankruptcy in ASEAN. Several countries in ASEAN are taking other ways to overcome this problem. This is done by entering into bilateral agreements or by adopting the UNCITRAL Model Law. Indonesia still does not strictly regulate transnational bankruptcy. Looking at the problems above, in this journal a comparison will be made regarding the resolution of transnational bankruptcy in Singapore, Malaysia and Indonesia as well as the application of international law in Indonesia in resolving transnational bankruptcy. This research was prepared with the aim of knowing and analyzing the legal regulations regarding transnational bankruptcy in ASEAN as well as identifying and analyzing the roots of obstacles to transnational bankruptcy in Indonesia. normative and comparative juridical approach methods, namely research that is focused on reviewing and comparing library materials or secondary data such as statutory regulations, international regulations, legal works using analytical descriptive research specifications and studied using qualitative data analysis methods. Based on the results of research and discussions carried out by analyzing decision Number 138/Pdt.Sus-PKPU/2016/PN.Niaga.Jkt.Pst, it was found that Indonesia has not regulated the mechanism for resolving transnational bankruptcy, so it is necessary to apply international law in resolving it by resorting to petition efforts. recognition and implementation of the bankruptcy decision in the country concerned.